2023
DOI: 10.1177/10398562231172398
|View full text |Cite
|
Sign up to set email alerts
|

Thinking clearly about climate change and mental health

Abstract: Objective To examine the quality and strength of evidence for an association between temperature increases caused by climate change and suicide used in policy documents to advocate for radical changes to healthcare systems in pursuit of decarbonisation. Method The designs of articles collected in a systematic review which concluded that there was an association between climate change and increased rates of suicide were analysed for their capacity to support this conclusion. Complete US data covering temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It is disappointing that Australasian Psychiatry has published an article by its deputy editor without disclosing any conflict of interest, particularly as the article insinuates biased presentation of evidence in the RANZCP statement on climate change. 1 , 2…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It is disappointing that Australasian Psychiatry has published an article by its deputy editor without disclosing any conflict of interest, particularly as the article insinuates biased presentation of evidence in the RANZCP statement on climate change. 1 , 2…”
mentioning
confidence: 99%
“…Amos’ article examined two of the 35 publications referenced in the RANZCP position statement ‘Mental health impacts of climate change’ and concluded that they were inadequate to support the statement. 1 He noted that although 16 of 17 observational studies found positive relationships between higher temperatures and increased rates of suicide, observational research cannot prove that climate change increases suicide rates. 1 However, the studies clearly demonstrate trends and provide adequate evidence for Thompson et al to support the assertion that rates of suicide are likely to increase in line with climate projections.…”
mentioning
confidence: 99%
See 3 more Smart Citations